PWE-130 Statin use and risk of malignant progression in patients with non-dysplastic barrett's oesophagus: a nested case-control study. (17th June 2017) - Alexandre, L; Royston, C; Caygill, C; Bhattacharjee, S; Dev, K; Clark, A; Watson, A; Hart, A
Abstract : Introduction: There are no established non-endoscopic evidence-based approaches to reduce the risk of malignant progression in patients with non-dysplastic Barrett's oesophagus (BO), the only known precursor to oesophageal adenocarcinoma (OAC). Statins exert plausible anti-carcinogenic mechanisms and are attractive potential chemoprotective agents. There is uncertainty in current estimates for associations between statin use and malignant progression in BO populations. This study aimed to investigate whether statin use is inversely associated with either high-grade dysplasia (HGD) or OAC in a BO population. Method: Participants diagnosed with BO with follow-up from 1 st January 2000 to 13 th June 2013 were identified from two contributing centres of the UK National Barrett's Oesophagus Registry (UKBOR). Patients with HGD and/or OAC were matched with up to two controls with non-dysplastic BO and no evidence of progression, for gender, centre and date of birth. Duration of follow-up was matched within each case-control set. Data on relevant exposures were extracted from hospital records. Statin use was measured between 6 months to 5 years prior to the date of diagnosis of each case and the equivalent index date in matched controls. Conditional logistic regression estimated associations between statin use and malignant progression, with adjustment for body mass index, smoking status, use of aspirin, NSAIDs, proton pump inhibitors and histamine receptor antagonists. Results: In total, 79 cases with HGD/OAC were matched to 138 controls with non-dysplastic BO. Statin use was equally prevalent (17.7%) in cases and matched controls. Statin use was not significantly associated with malignant progression in either unadjusted (OR 1.13, 95% CI 0.53–2.41) or adjusted analyses (OR 0.69, 95% CI 0.23–2.02). Dose and duration response relationships, defined with categories of mean statin dose (p for trend=0.758), cumulative dose (p for trend=0.289) and cumulative duration (p for trend=0.216) were all non-significant. Conclusion: No significant associations were demonstrated between statin use and risk of malignant progression in a BO population registered with UKBOR. Disclosure of Interest: None Declared